Ecotheology-Based Enforcement of Environmental Criminal Law: Integrating Positive Law and Islamic Law for Ecological Protection - Ahmad Mubarak (Justice Voice, 2026)
Environmental criminal law enforcement in Indonesia continues to face fundamental challenges, including weak deterrent effects, a predominant administrative orientation, and the suboptimal realization of ecological restoration as an objective of criminal punishment. At the same time, environmental degradation is not merely a legal issue but also has moral, spiritual, and theological dimensions, as it concerns the relationship between human beings, God, one another, and nature. This study aims to analyze ecotheology-based environmental criminal law enforcement by integrating Indonesian positive law with the principles of Islamic law. This study employs normative legal research using conceptual and statutory approaches. The legal materials examined comprise primary legal materials, including Law Number 32 of 2009, Law Number 6 of 2023, Government Regulation Number 22 of 2021, as well as Islamic legal sources derived from the Qur’an, hadith, and principles of Islamic jurisprudence (qawaid fiqhiyyah). Secondary legal materials were obtained from scholarly literature, judicial decisions, and reports issued by credible institutions. The findings indicate that ecotheology can strengthen the paradigm of environmental criminal law enforcement by positioning environmental pollution and degradation not only as violations of law but also as a betrayal of the human responsibility as khalifah (stewards) of the Earth. This approach promotes a model of criminal punishment that is not solely retributive but also preventive, restorative, educational, and transformative. The study concludes that ecotheology-based environmental criminal law enforcement is relevant to fostering ecological legal awareness, strengthening corporate accountability, and expanding the orientation toward environmental restoration as an integral component of ecological justice.